Manejo del herbicida pretilachlor en el cultivo de arroz (Oryza sativa - Murillo Santillán, Francisco Abrahám (2024)
Rice (Oryza sativa) is one of the most important foods worldwide since the majority of the population consumes it daily, which is why pretilachlor is a selective herbicide used mainly in rice cultivation to control a variety of weeds. It belongs to the group of chloroacetamides and is applied pre-emergence or early post-emergence. This research aims to describe the management of the herbicide pretilachlor in rice cultivation. This work was developed as a non-experimental bibliographic research using the analysis technique, magazines, current texts, articles, synthesis and summary of the collected data. The results obtained in the research show that the weeds controlled by pretilachlor are annual grasses, sedges and some dicotyledons. For the application of pretilachlor, various equipment is used, such as backpack sprayers, tractor-mounted sprayers and irrigation systems, ensuring uniform coverage. The effectiveness of pretilachlor in rice has been widely demonstrated in its mode of action which involves inhibiting the synthesis of essential fatty acids in weeds, thereby stopping their growth. It is essential to follow the dosage and application recommendations to avoid phytotoxicity in rice and minimize weed resistance with the appropriate equipment according to the size of the field and specific conditions since it is essential to maintain the effectiveness of pretilachlor and the sustainability of the crop. of rice.